145k views
4 votes
Simplify 1/y^-3 and identify the exponential property that you used

1 Answer

4 votes

Answer:

Thus,


(1)/(y^(-3))\:=y^3

Explanation:

Given the expression


(1)/(y^(-3))\:

simplifying the expression


(1)/(y^(-3))\:


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


=(1)/((1)/(y^3))


\mathrm{Apply\:the\:fraction\:rule}:\quad (1)/((b)/(c))=(c)/(b)


=(y^3)/(1)


\mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(1)=a


=y^3

Thus,


(1)/(y^(-3))\:=y^3

User MartinC
by
6.0k points